Home Prices, Fertility, and Early-Life Health Outcomes - N. Meltem Daysal; Michael Lovenheim; Nikolaj Siersbæk; David N. Wasser (Institute of Labor Economics (IZA), 2020)
We estimate the effect of housing price changes on fertility and early-life child health in Denmark. Using rich population register data among women aged 20-44 who own a home, we find that for each 100,000 DKK increase in home prices (equivalent to 12,000), the likelihood of giving birth increases by 0.27 percentage points or 2.32%. These estimates are similar to findings from the US per dollar of home price change, which is surprising given the strong pro-natalist policies and generous government programs in Denmark. We also present the first estimates of the effect of home prices on infant health. Our findings indicate that housing price increases lead to better child health at birth in terms of low birth weight and prematurity, however most of these effects reflect changes in the composition of births. There is no evidence of an effect on health during the first five years of life. These findings are consistent with a lack of credit constraints among homeowner families and with both children and child health being normal goods that are similarly-valued in the US and Denmark.
Keywords: J13; 330; housing wealth; fertility; child health; birth outcomes